Intention to use sharia e-commerce: Applying a combination of the technology acceptance model and theory of planned behavior - Afief El Ashfahany (19437031) (2023)
This study aims to build a framework for the variables affecting interest in sharia e-commerce, such as attitude, subjective norms, perceived behavior control, perceived usefulness, perceived ease of use, and religiosity. Using a convenience sampling method, this analysis involved 212 young people, who represent the most significant proportion of e-commerce clients. The survey measurements and hypotheses testing used the partial least square structural equation modeling (PLS-SEM) approach. The results of the study show that attitude (ß = 0.261, p = 0.000), subjective norm (ß = 0.264, p = 0.000), perceived usefulness (ß = 0.241, p = 0.013), and perceived ease of use (ß = 0.185, p = 0.032) have a positive relationship with intention to use sharia e-commerce for youths. In addition, perceived ease of use (ß = 0.759, p = 0.000) also significantly affects perceived usefulness as a moderator to intention. In comparison, perceived behavior control (ß = –0.042, p = 0.505) was an insignificant factor in using sharia e-commerce. This study also shows that religiosity (ß = 0.648, p = 0.000) is essential in a person’s attitude toward intending to use sharia e-commerce. The insignificant relationship between perceived behavior control and intention to use sharia e-commerce is believed to be because both conventional and sharia e-commerce are easily operated. Thus, youth people have not noticed many differences in using sharia e-commerce. Other Information Published in: Innovative Marketing License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.21511/im.19(2).2023.15